Staffing And The Psychology Of Leadership Power In Islamic Higher Education In Enhancing Human Resource Performance Management - Jamali; Nafi'a, Ilman; Gumiandari, Septi (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This research aims to describe the power psychology of leaders in IAIN Syekh Nurjati Cirebon in improving human resource performance management through staffing policies from 2015 to 2023. Through a Qualitative-Descriptive approach with a Case Study method, several data were obtained: (1) There were differences in the appointment of officials within the IAIN Syekh Nurjati Cirebon environment between the initial period and the second period under the leadership of Rector S. In the first period, the appointment of officials was based on input from Baperjakat (Position and Rank Consideration Board) established by Rector's Decree No. 73/In.14/R/Kp.07.6/03/2015, while in the second period, the Rector relied more on the selection mechanism through the Selection Committee's decree; (2) The power psychology of leadership in higher education institutions plays a significant role in the appointment of officials within the IAIN Syekh Nurjati Cirebon environment. As a result, there are several less positive tendencies in the appointment of officials in the environment as follows: (a) Placement of officials not based on qualifications, competencies, career experience, and human resource career levels; (b) Placement of officials violating applicable laws; (c) Lack of vigilance and precision in appointing officials; (d) Lack of appreciation for the performance of high-performing officials in previous periods; and (e) Potential nepotism in appointing employees; (3) Several proposed strategies and techniques to minimize the absolute power of management include: (a) Policies should be bottom-up, not top-down; (b) Top leadership's psychological control over policies that are not pro-quality; (c) conducting need assessment; (d) support from top leadership through other managerial education and training; and (e) improving the qualification system.